1999
DOI: 10.1086/315126
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniaeDNA Detection in Peripheral Blood Mononuclear Cells Is Predictive of Vascular Infection

Abstract: Abdominal aortic aneurysm tissue and peripheral blood mononuclear cells (PBMC) of 41 consecutive subjects undergoing abdominal aortic aneurysm surgery were analyzed by polymerase chain reaction (PCR) for the presence of Chlamydia pneumoniae, Mycoplasma pneumoniae, and Helicobacter pylori DNA. Twenty patients (49%) were positive for C. pneumoniae DNA-16 (39%) in both PBMC and aneurysm tissue, 3 (7.3%) in PBMC only, and 1 (2.4%) in the artery specimen only. Previous exposure to C. pneumoniae was confirmed in 19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
94
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 10 publications
9
94
1
Order By: Relevance
“…Previous studies reported different prevalence of CP by PCR in specimens obtained from abdominal aortic aneurysm, ranging from 20% to 49%. 4,5,6,7 Therefore our positivity rates are within the expected range. In our study, an optimized DNA extraction protocol to reduce any underestimation of CP prevalence was used, and our data were confirmed by nonradioactive DNA hybridization to enhance specificity.…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies reported different prevalence of CP by PCR in specimens obtained from abdominal aortic aneurysm, ranging from 20% to 49%. 4,5,6,7 Therefore our positivity rates are within the expected range. In our study, an optimized DNA extraction protocol to reduce any underestimation of CP prevalence was used, and our data were confirmed by nonradioactive DNA hybridization to enhance specificity.…”
Section: Discussionsupporting
confidence: 74%
“…Nasopharyngeal aspirate samples in 2 mL of transport medium containing a sucrose phosphate buffer were frozen at -708C. Nested polymerase chain reaction (PCR) was performed for both pathogens with validated methods, as previously described [17,18]. To avoid the risk of contamination, sample preparation, PCR amplification and product analysis were performed in separate rooms.…”
Section: Methodsmentioning
confidence: 99%
“…Touchdown nested PCR for detection of C. pneumoniae DNA was performed using primers designed to detect the major outer membrane protein [19]. Extracted DNA solution (10 mL in a total volume of 50 mL) was used in the first PCR round; 5 mL of the PCR products amplified by the outer primers was then transferred to a new 50-mL PCR reaction mix for a second amplification using the inner primers [18]. The first round consisted of 40 cycles and the second 35.…”
Section: Methodsmentioning
confidence: 99%
“…Nasopharyngeal aspirates were also obtained, immediately immersed in sucrose-phosphateglutamate transport medium, and stored at x70uC until assayed for the presence of M. pneumoniae and C. pneumoniae deoxyribonucleic acid (DNA). PCR for both pathogens was performed as previously described [16,17]. Chest radiographs (erect posteroanterior and lateral view) were taken in the hospital of admission and were then centrally reviewed by an experienced radiologist who was naive to the patients' clinical history or laboratory data.…”
Section: Methodsmentioning
confidence: 99%